Pemberdayaan BUMDes Desa Wotsogo melalui Pendampingan Budidaya dan Hilirisasi Jamur Kuping - Husnama Patih; Dina Anisya Rufaedah; Fadliyatul Muna; Nailatul Muna (Journal of Innovation and Contribution to Community Service, 2026)
This Community Service Program (PkM) aims to strengthen the wood ear mushroom (Auricularia auricula) cultivation business managed by the Village-Owned Enterprise (BUMDes) of Wotsogo Village, Jatirogo District, Tuban Regency, which is still in the early stage of development. The program employed a participatory community empowerment approach with a qualitative descriptive design to evaluate changes in the partner’s business capacity before and after the intervention. Data were collected through field observations, semi-structured interviews, and documentation, and were analyzed using qualitative descriptive analysis. The program was implemented in stages, including problem identification, the formulation and implementation of cultivation and post-harvest Standard Operating Procedures (SOPs), product downstreaming training, and assistance in business governance and marketing. The results indicate improvements in both technical and managerial capacities of the BUMDes, as reflected in more consistent SOP implementation, the initial development of value-added mushroom products, and better financial record-keeping and marketing practices. These findings confirm that participatory mentoring is effective in strengthening early-stage village enterprises and contributes to the development of a village-based local economy.